Use of NRCS Model Approach in a Watershed without Landcover Data - Choudhury , Parthasarathi; Nongthombam, Jotish (Research and Developments in Engineering Research Vol. 5, 2023)
This chapter highlights the application of NRCS Model to Watershed Having No Landcover Data. In the current study, the length and slope parameters of a watershed are used to apply the NRCS model with a velocity factor estimating technique. According to the properties of the Kirpich formula and velocity relationship, the length and slope data can be used to directly determine the flow velocity for a watershed. The model is applied to two ungauged watersheds, Madhura and Ghagra located in Barak basin in India to derive triangular UH applying NRCS technique. Drainage network for the watersheds and the geomorphologic parameters are estimated using 30m-ASTER DEM. Geographic Information System (GIS) is a potentially effective tool in modeling spatially varied systems. Most of the geomorphologic parameters that are required for developing UH for a watershed are spatially varied and many authors have used GIS in estimating geomorphic IUH/UH for a watershed. Length and average slope values for the watersheds are estimated using GIS technique. Peak UH results produced using the model are contrasted with prior GIUH results; a comparison of the model performances reveals that the NRCS model performs similarly when the velocity factor is calculated using length and slope variables. Watersheds that are not gauged and for which there are no data on land cover characteristics will benefit from the incorporation of the novel velocity estimation technique into the NRCS model.